Heart rate variability as a marker of term adaptation mechanisms in predicting an individual adaptation to the balneotherapy - Povetkina, T. M.; Gozhenko, E. A.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Povetkina T. M., Gozhenko E. A., Zukow W. Вариабельность сердечного ритма как маркер срочных механизмов адаптации в прогнозировании индивидуального приспособления к бальнеотерапии = Heart rate variability as a marker of term adaptation mechanisms in predicting an individual adaptation to the balneotherapy. Journal of Education, Health and Sport. 2015;5(1):249-262. ISSN 2391-8306. DOI: http://dx.doi.org/10.5281/zenodo.32298 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A249-262 https://pbn.nauka.gov.pl/works/657835 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2015. Revised 18.01.2015. Accepted: 21.01.2015. ВАРИАБЕЛЬНОСТЬ СЕРДЕЧНОГО РИТМА КАК МАРКЕР СРОЧНЫХ МЕХАНИЗМОВ АДАПТАЦИИ В ПРОГНОЗИРОВАНИИ ИНДИВИДУАЛЬНОГО ПРИСПОСОБЛЕНИЯ К БАЛЬНЕОТЕРАПИИ Heart rate variability as a marker of term adaptation mechanisms in predicting an individual adaptation to the balneotherapy Повєткіна Т. М.1, Гоженко О. А.1, Zukow W.2 Povetkina T. M.1, Gozhenko E. A.1, Zukow W.2 1SE Ukrainian Scientific Research Institute of Medical Rehabilitation and Balneology Ministry of Health of Ukraine, Odessa, Ukraine 1ГУ «Украинский научно исследовательский институт медицинской реабилитации и курортологии МЗ Украины», г. Одесса, Украина 2Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland 2Wydział Kultury Fizycznej, Zdrowia I Turystyki, Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska Резюме: За характеристиками варіабельності серцевого ритму (ВСР) аналізували адаптаційні реакції практично здорових чоловіків молодого віку до однократного внутрішнього вживання гідрокарбонатно-магнієво-кальцієвої, слабко-мінералізованої мінеральної води (МВ) Нафтуся. Реакція термінової адаптації до 20-ї хв. супроводжується активацією нейрогуморальної регуляції, а саме помірним збільшенням тонусу парасимпатичного та симпатичного відділів ВНС, значним напруженням систем регуляції та підвищенням рівня інсуліну, з переходом до 60-ї хв. до нормотонії, та формуванням стрес-лімітуючої дії бальнеочинника. Виявлено два варіанти реакції вегетативної реактивності, яка до 60-ї хв. змінюються протилежно: надмірна, за симпатичним типом з пригніченням центрального впливу на регуляцію, або парасимпатичним типом – з виразним перевантаженням центральної ланки регуляції. Ключові слова: термінова адаптація, бальнеотерапія, варіабельність серцевого ритму. Summary According to the characteristics of the heart rate variability (HRV) analyzed adaptation reaction practically healthy men of young age to-internal use of hydrocarbonate magnesium-calcium, weakly-mineralized mineral water (MW) Naftusia. The reaction of active adaptation to the 20th minute. accompanied by activation of neurohumoral regulation, namely a moderate increase in sympathetic tone and parasympathetic divisions of vegetative nervous system, significant stress systems of regulation and increasing the level of insulin, with the transition to the 60th minute. to normotonia, and the formation of stress limit action balneal factor. Detected two variants of reaction of the autonomic reactivity, which up to 60th minute. changing the opposite: excessive for the type of sympathetic central inhibition effect on regulation or parasympathetic type - with an expressive overload central level overload regulation. Keywords: urgent adaptation, balneotherapy, variable heart rate.